Morphological diversification of alien and native aquatic snails of the genus Physa and Aplexa (Gastropoda: Physidae) of Western and Central European range - Cieplok, Anna; Anderson, Roy; Gawlak, Magdalena; Kałuski, Tomasz; Spyra, Aneta (Zootaxa, 2022)
This is the first comparative study on alien and native Physidae (Gastropoda: Heterobranchia) from Western and Central Europe. Morphology, ecological features and distribution are presented for each physid species. We analysed taxonomical features of physid snails from Europe in great detail. Scanning electron microscopy (SEM) methods were used to elucidate the external morphology of the shells of physid gastropods that occur in Western and Central Europe. On comparison we found significant differences in the external morphology among the species. Morphological analyses facilitate the recognition of variations of physid shells. An interspecific similarities were noted within Physidae while interspecific differences were identified in the morphology of apex and spires. The lowest intraspecific variability in shells was noted between particular individuals of P. fontinalis and A. hypnorum. The most characteristic features and differences of representatives of Physidae are presented and discussed. This is especially important for the identification of Physa gyrina and the worldwide invasive species Physa acuta which resemble each other in shape and are difficult to distinguish. We also present a new identification key for physid species, including the results of ecological assessment and discuss current distribution of these species in Europe.